The Development of Character Education in Papua: An In-Depth Analysis of the Current Progress and Challenges - Silaban, Rusdiana (International Journal of Education and Digital Learning (IJEDL), 2023)
Character education in Papua, Indonesia, has become a focal point of educational reform. Papua, with its rich cultural diversity and challenges, presents unique opportunities and hurdles in the advancement of character-building practices within its educational system. This study examines the development of character education programs in Papua, analyzing their implementation, successes, and challenges in comparison to other regions in Indonesia. Data was collected from government reports, educational policies, and interviews with local educators. The research highlights the importance of integrating local culture and values in character education, alongside the national curriculum. Furthermore, it explores the role of community engagement in fostering a supportive environment for character education. The findings suggest that while significant progress has been made, challenges related to infrastructure, teacher training, and the integration of indigenous values remain. The study concludes with recommendations for improving the effectiveness of character education in Papua, aiming to create a more holistic educational experience for students.